2013
DOI: 10.1186/1475-2891-12-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: High bioavailablilty iron maize (Zea mays L.) developed through molecular breeding provides more absorbable iron in vitro (Caco-2 model) and in vivo (Gallus gallus)

Abstract: BackgroundIron (Fe) deficiency is the most common micronutrient deficiency worldwide. Iron biofortification is a preventative strategy that alleviates Fe deficiency by improving the amount of absorbable Fe in crops. In the present study, we used an in vitro digestion/Caco 2 cell culture model as the guiding tool for breeding and development of two maize (Zea mays L.) lines with contrasting Fe bioavailability (ie. Low and High). Our objective was to confirm and validate the in vitro results and approach. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 48 publications
3
51
0
2
Order By: Relevance
“…3 Values are mean ± SEM (cumulative weekly from day 0). 4,5 Fe bioavailability was calculated as hemoglobin maintenance efficiency ( HME ) [5-9,15]: HME=HbFe,mgitalicfinal-HbFe,mgitalicinitialTotalFeIntake,mg×100. Where Hb-Fe = total body hemoglobin Fe. Hb Fe was calculated from hemoglobin concentrations and estimates of blood volume based on body weight (a blood volume of 85 mL per kg body weight is assumed) [5-9,15,22]: Hb - Fe(mg) = B. W. (kg) × 0.085 L blood/kg  ×  Hb (g/L) × 3.35 mg Fe/g Hb.…”
Section: Resultsmentioning
confidence: 99%
“…3 Values are mean ± SEM (cumulative weekly from day 0). 4,5 Fe bioavailability was calculated as hemoglobin maintenance efficiency ( HME ) [5-9,15]: HME=HbFe,mgitalicfinal-HbFe,mgitalicinitialTotalFeIntake,mg×100. Where Hb-Fe = total body hemoglobin Fe. Hb Fe was calculated from hemoglobin concentrations and estimates of blood volume based on body weight (a blood volume of 85 mL per kg body weight is assumed) [5-9,15,22]: Hb - Fe(mg) = B. W. (kg) × 0.085 L blood/kg  ×  Hb (g/L) × 3.35 mg Fe/g Hb.…”
Section: Resultsmentioning
confidence: 99%
“…However, a genetic approach may not always be adequate due to several interacting factors, including lack of readily available germplasm, unfavorable genetic, physiological, and chemical interactions within the ionome [38], and negative relationships with grain yield [17,20]. These perceived shortcomings of genetic biofortification recently led to promoting molecular breeding [38,39] as a means of improving [nutrient] and bioavailability of micronutrients in maize and other grain crops.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its high heritability, only three modest QTL for FeGC were detected, which confirms that this trait is under the control of many small QTL (Šimić et al 2012), whereas there were ten QTL for FeGB accounting for 54 % of the variance observed in samples from a single year/location trial. In vitro digestion/Caco 2 cell culture and in vivo poultry models were used to compare maize lines with contrasting Fe bioavailability (Tako et al 2013). A favorable matrix for absorption could explain the Fe-bioavailability levels among these lines.…”
Section: Genomics-led Improvement For Enhancing Genetic Gainsmentioning
confidence: 99%